KEPEKAAN ARUS INRUSH PADA KERJA RELE DIFERENSIAL TRANSFORMATOR DAYA DI GARDU INDUK DURI KOSAMBI - Irvan Buchari Tamam; Agung Hariayanto; Harian Puteri Lokastithi (Sutet, 2015)
At the time a given voltage power transformer there will be symptoms of transient inrush magnetization. This magnetization inrush can cause the magnetization inrush current at power transformer primary coil. This inrush currents perceived as a fault, and therefore at the same time differential relay can not distinguish them from the real fault current, the inrush current will be seen as an internal disorder which should be extinguished. Overcome the inrush current method is to delay, detain or block the relay so that the differential element during transient inrush relay state is not going to work. In this paper will be discussed studies on the effects of inrush current at the differential relay in substation duri kosambi.